Community Assistance for Forest and Land Fire Prevention (Karhutla) in Gelebak Dalam Village, Banyuasin District, South Sumatra - Tarmizi, Yenrizal; Sirozi, Muhammad (University of Merdeka Malang, 2020)
Forest and land fires (karhutla) are events that always occur every year in Indonesia. South Sumatra is one of the regions contributing to the forest and land fires. Various attempts have been made but it still does not work. This paper aims to describe other methods of dealing with forest and land fires, namely the assistance method. Its location is in Gelebak Dalam Village, South Sumatra. The method used is participatory action research. The results show that community participation is able to prevent forest and land fires and create new methods in assistance.Â DOI: https://doi.org/10.26905/lw.v12i1.3586 Â